The effects of upper and lower limb elastic band training on the change of direction, jump, power, strength and repeated sprint ability performance in adolescent female handball players - Gaamouri, N.; Hammami, M.; Cherni, Y.; Oranchuk, D. J.; Bragazzi, N.; Knechtle, B.; Chelly, M. S.; Van Den Tillaar, R. (Frontiers in Sports and Active Living, 2023)
This study aimed to examine the effects of incorporating 10-week elastic band strength training (EBST) program on change of direction, jumping ability, repeated sprint ability, and both muscular strength and power in adolescent female handball players. Participants aged 15.8 ± 0.2 years were divided by playing position, and players from each position were then randomly assigned between the elastic strength (n = 17) and control (n = 17) groups. The experimental group performed periodized upper and lower-body elastic band strength training twice weekly for ten weeks by substitution of some of their regular physical and game preparation. The control group only performed regular handball training. Two-way analyses of variance (group × time) assessed change of direction (COD) via the modified t-agility test, squat jump, countermovement jump, standing long jump, repeated sprint ability (RSA), 1-RM bench press and half squat, and cycle ergometer force-velocity tests for both upper and lower limbs. Relative to the control group, the experimental group enhanced COD performance [p < 0.001; Cohen's effect size (d) = 1.00]; squat and countermovement jump (p = 0.002, d = 0.83), best, mean, and total RSA scores (all p < 0.001, d = 0.92-1.66), 1-RM bench press (p = 0.02, d = 0.59) and half squat (p = 0.009, d = 0.67), all indices of upper limb force-velocity performance (p = 0.025, d = 0.56-1.66), and 3 of 4 indices of lower limb force-velocity performance (p = 0.004, d = 0.75-0.92). We conclude that additional elastic band training performed twice a week for ten weeks improves measures relevant to handball game performance in adolescent female athletes.